Contamination of soil with heavy metals in industrial districts of Kokshetau - Tazitdinova, R.M.; Beisenova, R.R.; Grigoryev, A.I.; Issayenko, O.P. (Fundamental and Experimental Biology, 2019)
The article reveals the research results on soil contamination with heavy metals of Kokshetau and Vasilkovsky gold ore deposit. Soil contamination with heavy metals is of a high danger due to the fact that soils are able to actively accumulate heavy metals. Heavy metals can further soak into plant and animal organisms straight from the soil, and then ultimately intothe human body. Main soil pollutants such as zinc, copper and arsenic were identified with arsenic being the main contaminant. As a result of the research, the map was compiled, where the trial sites was marked and zinc, copper and arsenic concentrations in the soils of the industrial areas of the city and beyond was identified. It was found that in the industrial areas of Kokshetau and influence zone of Vasilkovsky gold ore deposit the soils were mostly contaminated with arsenic, and significant excess of zinc and copper maximum permissible concentrations were noted. Zinc concentration exceeded MPC value from 3 to 8 times, copper exceeded from 2 to 22 times, arsenic exceeded from 7 to 361 times.